Effects of VLS and VS mechanisms during shell growth in GaAs-AlGaAs core-shell nanowires investigated by transmission electron microscopy. (July 2017) - Scuderi, Mario; Prete, Paola; Lovergine, Nico; Spinella, Corrado; Nicotra, Giuseppe
Abstract: We investigated by means of transmission electron microscopy (TEM) the final growth stage of GaAs/AlGaAs core-shell nanowires (NWs) self-assembled by Au-catalyst assisted metalorganic vapor phase epitaxy (MOVPE). TEM observations and energy dispersive x-ray spectroscopy revealed the presence of an AlGaAs tapered region of varying chemical composition nearby the NW extreme end (i.e. between the core-shell NW trunk and the Au nanoparticle catalyst). Our findings evidence that this region exhibits an unintentional Aly Ga1−y As/Alx Ga1−x As core-shell structure, a result of the combined axial (vapor-liquid-solid, VLS) self-assembly and conventional (vapor-solid, VS) overgrowth of the material. While the VS-grown Alx Ga1−x As alloy retains the Al composition (x=0.3) of the AlGaAs shell along the NW trunk, the central Aly Ga1−y As section is made of an Al-rich (y≈0.8–0.9) alloy segment formed during AlGaAs shell overgrowth, followed by a graded-alloy segment formed upon deposition of the terminating GaAs cap layer, the latter segment due to the effect of the Al reservoir left in the Au catalyst nanoparticle (NP).